Suriname : 2008 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion for Suriname; and Statement by the Executive Director for Suriname. (IMF Staff Country Reports; Country Report, 2008)
The key findings of Suriname's 2008 Article IV Consultation show that a narrow economic base, terms-of-trade swings, and a weak policy/institutional framework have in the past led to macroeconomic instability. Weak policy and institutional frameworks have contributed to higher economic volatility and lower growth than in other commodity-exporting countries. These have undermined the credibility of policies and contributed to high financial dollarization, with over half of deposits denominated in foreign currency. Aided by high commodity prices and improved confidence, GDP growth is estimated at 5 1\2 percent, with strong performance in both the mineral and nonmineral sectors.